Testicular “Hyperstimulation” Syndrome: A Case of Functional Gonadotropinoma - Astha Thakkar; Subramanian Kannan; Amir Hamrahian; Richard A. Prayson; Robert J. Weil; Charles Faiman (Case Reports in Endocrinology)
Gonadotropins secreting pituitary tumors tend to present as sellar mass with hypogonadism. Biologically active LH secretion by these tumors resulting in elevated testosterone is extremely rare. We report a case of a 48-year-old male patient who presented with giant pituitary tumor, elevated testosterone, and elevated levels of gonadotropins. Surgical resection of the tumor resulted in normalization of gonadotropins and fall in serum testosterone to subnormal levels in the postoperative period confirming that the tumor was secreting bioactive luteinizing hormone (LH).